A Safety Monitoring Instrument Based on SPMC75F2313 for Traction Motor - LIU Ju-ping; YU Wei-qing; TANG Zhao-ping (机车电传动)
Based on SPMC75F2313 as control core, using hall sensor to sampling traction motor current in real-time, and with interpretation of the current bias and temporal scales, motor status was determined. When traction motor fault occurred, such as pinion loosening, shaft broken and so on, the monitoring device could accurately alarm and record the fault information, to remind attendants dealing with the fault for preventing accident spreading.